2018
DOI: 10.1007/s10493-018-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mulch layer on the assemblage and abundance of mesostigmatan mites and other arthropods in the soil of a sugarcane agro-ecosystem in Australia

Abstract: Sugarcane farmers can utilise a soil conservation technique called green cane trash blanketing, a form of mulching that can increase plant productivity through a number of channels, e.g., via altering soil physical, chemical and biological characteristics, and influence soil arthropod assemblages. Predatory mites (Mesostigmata) are important components of soil communities because they can control populations of other soil-dwelling pest species. Our aim was to characterise mulch-influenced predatory Mesostigmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…Since our survey results showed that cane fields with mulch layers tended to have higher populations of microarthropods in mineral soil than fields where the mulch had been removed, and this was consistent with the findings of Manwaring et al (2018), we assumed that mulching was providing a soil moisture and temperature environment that favoured these animals. Thus, we were surprised that there was no significant difference in the number of microarthropods recovered from mulched and bare soils in our field experiments.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since our survey results showed that cane fields with mulch layers tended to have higher populations of microarthropods in mineral soil than fields where the mulch had been removed, and this was consistent with the findings of Manwaring et al (2018), we assumed that mulching was providing a soil moisture and temperature environment that favoured these animals. Thus, we were surprised that there was no significant difference in the number of microarthropods recovered from mulched and bare soils in our field experiments.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies in natural and agricultural ecosystems have shown that the abundance and diversity of microarthropods is influenced by factors such as soil texture, soil carbon levels, depth in the soil profile and the presence of plant residues on the soil surface, and all these factors could have affected our survey results. Consequently, we set up field experiments to look at the impact of mulching, as it is a common practice in the Australian sugar industry and our survey data suggested that the presence of mulch (the residues remaining after harvest and referred to as a 'trash blanket' in Australia) may have increased the abundance of microarthropods (see also Manwaring et al 2018). We also set up a pot experiment to determine whether properties such as the texture of sugarcane soils affected the presence and diversity of mites.…”
Section: Introductionmentioning
confidence: 99%
“…Leguminous species, such as Crotalaria spectabilis Roth and Mucuna pruriens (L.) DC., can increase macroarthropod richness (e.g., on average 200% higher species richness and 140% higher Shannon's diversity index than in non-legume species) (Melo et al 2019). Understanding the effect of the addition of these legumes which may regulate the macroarthropod diversity in a semi-arid ecoregion is essential to explain why soil fauna groups (e.g., litter transformers, herbivores and predators) become less frequent during the dry season (Manwaring et al 2018;Roy et al 2018;Nunes et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the effect of the addition of legumes that may regulate the macroarthropod diversity and richness from a 3years field experiment on a Regosol is essential to explain why the long-term cultivation of non-legume plant species becomes less beneficial to belowground soil organisms and their interaction with plant biomass production, soil organic carbon, and biodiversity than the cultivation of legume plant species in the same conditions (Coyle et al 2017;Manwaring et al 2018;Roy et al 2018). Over time, the cultivation of non-legume plant species under conventional farming system may result in a decline of soil organic carbon, plant biomass production and macroarthropod richness (Amazonas et al 2017;Souza et al 2018).…”
Section: Introductionmentioning
confidence: 99%